2022
DOI: 10.1089/3dp.2021.0176
|View full text |Cite
|
Sign up to set email alerts
|

Effective Mechanical Properties of AlSi7Mg Additively Manufactured Cubic Lattice Structures

Abstract: Lattice structures, whose manufacturing has been enabled by additive technologies, are gaining growing popularity in all the fields where lightweighting is imperative. Since the complexity of the lattice geometries stretches the technological boundaries even of additive processes, the manufactured structures can be significantly different from the nominal ones, in terms of expected dimensions but also of defects. Therefore, the successful use of lattices needs the combined optimization of their design, structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…More specifically, the size effect influences the mechanical properties through a specific scaling law formula. According to the existing literature [ 19 , 20 , 21 ], the effective mechanical properties of every architected material are dependent on the applied relative density in exponential relation via the aforementioned scaling laws. Furthermore, lattice structures, with intense exponential relation ( n > 2) between the mechanical properties and relative density, reveal low stiffness and strength with an extensive plateau after the yield point at the stress–strain diagram; this mechanical response is defined as bending-dominated behavior [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the size effect influences the mechanical properties through a specific scaling law formula. According to the existing literature [ 19 , 20 , 21 ], the effective mechanical properties of every architected material are dependent on the applied relative density in exponential relation via the aforementioned scaling laws. Furthermore, lattice structures, with intense exponential relation ( n > 2) between the mechanical properties and relative density, reveal low stiffness and strength with an extensive plateau after the yield point at the stress–strain diagram; this mechanical response is defined as bending-dominated behavior [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[21] New approaches are proposing the adoption of neural networks that allow tuning the desired mechanical response in much shorter computational times. [22] Simulation is addressed in many studies today [10,18,[23][24][25] with a special attention to the development of plastic and damage models.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The need for a standard characterization protocol for the assessment, preliminary to mechanical testing, of the lattice dimensions and microstructure, is well recognized in literature. [20] The authors' previous contributions [23,27] reported the manufacturability and numerical/experimental compressive behavior of body-centered cubic unit cells, with the addition of reinforcement beams in the X, Y, and Z directions (BCCxyz, Figure 1a). It emerged that horizontal beams (i.e., the beams along X and Y DOI: 10.1002/adem.202201074…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations